Silver Nanoclusters And Nanofractals In Natural Rubber Matrix. - Abu Bakar, N. H. H.; Ismail, J.; Abu Bakar, M. (2004)
Silver nanocrystals were synthesized in natural rubber matrix via UV irradiation technique. A high intensity UV light with a wavelength below 300 nm was used to reduce the silver ions in the natural rubber matrix.